Relativistic Electron Acceleration and the “Ankle” Spectral Feature in Earth’s Magnetotail Reconnection - Weijie Sun; Mitsuo Oka; Marit Øieroset; Drew L. Turner; Tai Phan; Ian J. Cohen; Xiaocan Li; Jia Huang; Andy W. Smith; James A. Slavin; Gangkai Poh; Kevin J. Genestreti; et al. (The Astrophysical Journal Letters)
Electrons are accelerated to high, nonthermal energies during explosive energy-release events in space, such as magnetic reconnection. However, the properties and acceleration mechanisms of relativistic electrons directly associated with the reconnection X-line are not well understood. This study utilizes Magnetospheric Multiscale (MMS) measurements to analyze the flux and spectral features of subrelativistic to relativistic (∼80–560 keV) electrons during a magnetic reconnection event in Earth’s magnetotail. This event provided a unique opportunity to measure the electrons directly energized by the X-line as MMS stayed in the separatrix layer, where the magnetic field directly connects to the X-line, for approximately half of the observation period. Our analysis revealed that the fluxes of relativistic electrons were clearly enhanced within the separatrix layer, and the highest flux was directed away from the X-line, which suggested that these electrons originated directly from the X-line. Spectral analysis showed that these relativistic electrons deviated from the main plasma sheet population and exhibited an “ankle” feature similar to that observed in galactic cosmic rays. The contribution of “ankle” electrons to the total electron energy density increased from 0.1% to 1% in the separatrix layer though the spectral slopes did not exhibit clear variations. Further analysis indicated that while these relativistic electrons originated from the X-line, they experienced a nonnegligible degree of scattering during transport. These findings provide clear evidence that magnetic reconnection in Earth’s magnetotail can efficiently energize relativistic electrons directly at the X-line, providing new insights into the complex processes governing electron dynamics during magnetic reconnection.